Evaluation of the impact, treatment patterns, and patient and physician perceptions of vasomotor symptoms associated with menopause in Europe and the United States. (October 2022) - Stute, Petra; Cano, Antonio; Thurston, Rebecca C.; Small, Mark; Lee, Lauren; Scott, Megan; Siddiqui, Emad; Schultz, Neil M.
Highlights: Vasomotor symptoms associated with menopause adversely affected sleep, mood, and quality of life. In this study, over 25 % of women with vasomotor symptoms had never received prescription treatment. Despite physicians' positive views of hormone therapy, many patients had negative views of it. Many women with vasomotor symptoms had poor symptom control or were dissatisfied with treatment. There is a need for improved management of vasomotor symptoms associated with menopause. Abstract: Objectives: This study elicited the views of physicians and patients with vasomotor symptoms (VMS) associated with menopause on the impact of VMS and treatment patterns/perceptions. Study design: Data from the Adelphi VMS Disease Specific Programme, a point-in-time survey conducted in 5 European countries and the United States in 2020, were used. Primary care providers (PCPs) and gynecologists seeing ≥3 patients/week with VMS associated with menopause completed a survey and chart review; their patients were invited to complete a survey and questionnaires. Main outcome measures: Physicians reported treatment patterns and patient-specific symptoms and treatment preferences. Patients described symptoms, impact of VMS, and treatment satisfaction. Results: Participants included 115 PCPs and 118 gynecologists. Physicians reviewed the charts of 1816 patients, 854 of whom completed surveys. Moderate/severe impact of VMS on sleep, mood, quality of life, and work/study was reported by 35.8 %, 31.6 %, 23.6 %, and 15.4 % of women, respectively. Based on chart review, 64.8 % of women were currently prescribed treatment for VMS, most commonly hormone therapy (HT; 73.1 %), followed by selective serotonin or serotonin-norepinephrine reuptake inhibitors (31.3 %). Most women (57.3 %) with VMS were eligible for HT but averse to using it. Despite 91.4 % of physicians finding HT to be effective, 62.7 % agreed (slightly–strongly) that their patients are generally reluctant to use it. One-third of women were dissatisfied with VMS control. Conclusions: VMS can considerably impact daily life. Effective treatment options that are better accepted could potentially improve management of VMS and lead to better quality of life for women with VMS associated with menopause. Clinical trial registration: None.